A STUDY OF SOME ECONOMIC TRAITS OF MAMESH SHEEP IN ERBIL - Salm Omar Raaof (Mesopotamia Journal of Agriculture)
This work was carried out on 77 Iranian Mamesh sheep raised at private flock in Erbil plain to study the effect of some non - genetic factors on Birth Weight (BW), Weaning Weight (WW), Daily Gain (DG) on Milk Production (MP). The overall means of BW, WW, DG and MP were 4.99 kg ,30.44 kg ,0.283 kg and 894.85g, respectively .Type of birth ,sex of lamb ,weight and age of dam affected BW,WWand DG significantly (P <0.01) .Type of birth , stage of lactation and age of dam affected MP significantly (P<0.01) .It is concluded that performance of Mamesh sheep in Erbil is accepted .